FAKTOR-FAKTOR AGENCY THEORY YANG MEMPENGARUHI HUTANG - Farah Margaretha; Andhini Asmariani (Media Riset Bisnis & Manajemen, 2009)
The study's purpose is to acknowledge the factors that influence the company's total debt ratio. The samples are family business and non-family business which listed in Indonesian Stock Exchange (BEI) for the period of 2001 up to 2007. Independent variables in this study included percentage of insider shareholding, number of shareholders, family business with control variables are firm size, firm age, growth, asset structure, profitability, and industry classification. Meanwhile, dependent variable is total debt ratio.With using purposive sampling, the total of sample in this study is 16 of companies. Data analysis model are classic assumption test, ordinary least square regression and t-test. Based on t-test, the result of number of shareholders, family business, firm size, asset structure, firm age and industry dassification (hotel and travel services, credit agencies other than bank, food and beverages, adhesive) affect to total debt ratio.Keywords : Debt ratio, Agency theory, Capital structure